The Role of PGRI in Strengthening Educators’ Competencies Through the Continuing Professional Development Program - hasani, abdul azis; Fatmawati Rahimah; Gilang Rakha Faiza; Rosyidah Mei Noni (Universitas Negeri Semarang, 2025)
This study aims to examine the role of the Indonesian Teachers Association (Persatuan Guru Republik Indonesia/PGRI) in strengthening teachers’ professional competence at the regional level. The research employs a descriptive qualitative approach through interviews with administrators of the PGRI Special Region of Yogyakarta, as well as organizational document analysis. The findings indicate that PGRI plays its role through continuous training programs, the strengthening of teacher learning communities, mentoring in the development of instructional materials, and advocacy for teachers’ welfare and professional protection. However, the optimization of this role still faces obstacles, including variations in members’ levels of participation, limited funding, and uneven dissemination of program information across educational institutions. These findings underscore the need for strategies to strengthen internal coordination structures and to design more targeted competency development programs that are based on teachers’ needs.